Identifying the Impacts of Acne: A Delphi Survey of Patients and Clinicians. Issue 3 (May 2020) - Tan, Jerry; Frey, Marc P.; Thiboutot, Diane; Layton, Alison; Eady, Anne
Background: Acne can adversely impact those affected in multiple dimensions. The purpose of this study was to determine the most prominent impacts identified by acne patients and by clinicians. Methods: Independent Delphi surveys for acne patients and clinicians were conducted to achieve consensus regarding acne impacts within each group. Acne patients were recruited from outpatient clinics of authors (AL, JT, and DT). The first phase involved qualitative responses, where emergent themes were identified and used to generate items for 2 subsequent phases. Results: The qualitative phase generated 64 items in 3 themes: psychological, sociological, and treatment related. These items were independently ranked in importance by patients and by clinicians. Consensus for importance was achieved for 34 items by patients and 43 by clinicians. Patient-identified highest ranked items were being self-conscious, feeling unattractive, feeling uncomfortable in own skin, unattractive to others, would not want pictures taken, envious of people with clear skin, and time/effort spent concealing scarring; while clinicians identified feeling unattractive. Conclusions: We identify acne impacts within psychological, sociological, and treatment-related domains by acne patients and clinicians. Further, we establish discrepancies between patients and clinicians regarding the impact of acne. This provides evidence for the importance of establishing patient-reported outcomes.